Exploring the effects of isothiocyanates on chemotherapeutic drugs. (January 2014) - Minarini, Anna; Milelli, Andrea; Fimognari, Carmela; Simoni, Elena; Turrini, Eleonora; Tumiatti, Vincenzo
Abstract : Introduction: Chemoprevention has emerged as a promising strategy to reduce the risk and to control cancer. In this context, isothiocyanates (ITCs), found in abundance in the form of glucosinolates in cruciferous vegetables, have gained increasing consideration for their chemopreventive activity. ITCs exert their effects mainly by inducing carcinogen metabolism or by inhibiting tumor cell proliferation. Areas covered: In recent years, novel combination treatments, by coupling chemopreventive agents and typical chemotherapeutics, have been exploited to increase the antitumor activities. The aim of this article is to examine the foremost studies carried out, so far, on the effects of dietary and synthetic ITCs on different signaling pathways involved in the pharmacokinetics and pharmacodynamics of chemotherapeutic agents, in order to enhance their effectiveness. Expert opinion: Undoubtedly, the beneficial anticarcinogenic potential of ITCs, both singly and in combination, has emerged in in vitro and in vivo studies. However, only a few clinical trials have been carried out so far with ITCs, which try to better define both the pharmacokinetic and pharmacodynamic impacts in humans. More toxicological evaluations after long-term administration of ITCs in different species are required for the clinical development of ITCs as anticarcinogenic agents.